KRAS-Mutant Non-Small Cell Lung Cancer: An Emerging Promisingly Treatable Subgroup - Xie, Mingying; Xu, Xiaoling; Fan, Yun (Frontiers in Oncology, 2021)
Lung cancer, the leading cause of cancer-related deaths worldwide, can be divided into small cell lung cancer and non-small cell lung cancer (NSCLC), of which NSCLC is the most common histological type, accounting for 85% of all lung cancers. Kirsten rat sarcoma viral oncogene (KRAS) mutations are common in NSCLC but are associated with poor prognosis for patients. This is due to poor response to most systemic therapies and lack of targeted drugs. Currently, the latest published clinical trial data of the new small-molecule KRAS G12C inhibitors, AMG510 and MRTX849, indicate that these molecules may potentially be used for KRAS-mutant NSCLC treatment. Simultaneously, within the immuno-therapeutic process, immune efficacy has been observed in those patients who have KRAS mutations. In this article, the pathogenesis, treatment status, progress of immunotherapy, and targeted therapy of KRAS-mutant NSCLC are reviewed.